Ultrahigh-Speed Signal Transmission Over Nonlinear and Dispersive Fiber Optic Channel: The Multicarrier Advantage - William Shieh; Yan Tang (IEEE Photonics Journal, 2010)
There is a common belief that coherent optical orthogonal frequency-division multiplexing (CO-OFDM) has inferior nonlinear performance in the fiber optic channel due to its high peak-to-average power ratio (PAPR). In this paper, we show that due to the uniqueness of chromatic dispersion in the optical fiber, properly designed CO-OFDM can, in fact, possess a nonlinearity advantage over a coherent single carrier (SC) for ultrahigh-speed transport at 100 Gb/s and beyond. In particular, we propose a novel approach called multiband DFT-spread OFDM (MB-DFT-S-OFDM), by which the DFT-S-OFDM is applied to each subband of the multiband CO-OFDM to reduce the PAPR within each subband. It is found that eight-band DFT-S-OFDM surpasses the conventional OFDM and the coherent SC by 1.3 and 0.5 dB, respectively, for SSMF107-Gb/s transmission over a 1000-km standard-single-mode-fiber (SSMF).